Substance Use, Poor Sleep, and Gestational Diabetes: Concerns in Adolescent Pregnancy - Dokkedal-Silva, Vinícius; Hirata, Aparecida E.; Berro, Laís F.; Galduróz, José C. F.; Tufik, Sergio; Andersen, Monica Levy (Sleep Science, 2025)
Adolescence is a stage of development in which several social and biological parameters change drastically. Behavioral alterations are common during puberty, including the appearance of risk-taking behaviors such as substance use and unprotected sex, which can lead to unintended pregnancy. Of note, in addition to the inherent risks of pregnancy at a young age, sleep impairment and substance use are commonly seen in adolescents, even during pregnancy. The increased risk for the development of gestational diabetes, which has been linked to both sleep impairment and drug use, further complicates this scenario and deserves consideration among the scientific community and in the clinical setting. Therefore, in this commentary, we discuss the pathways connecting the risk of substance misuse, sleep impairment, and the development of gestational diabetes, a network that demonstrates the vulnerability of the pregnant teenage population. Future studies evaluating the complicating factors and modulators of pregnancy outcomes in these individuals are of the utmost importance.
Keywords: sleep; gestational diabetes; substance use disorder; adolescent pregnancy